Peningkatan Pengetahuan dan Kesadaran Hukum Hak Waris Anak Dalam Perkawinan Negen Dadua di Kelurahan Semarapura Kaja, Klungkung - Putu Ayu Sriasih Wesna; I Nyoman Sujana; Komang Arini Styawati; I Nyoman Sukandia; Anak Agung Istri Agung (Postgraduated Community Service Journal, 2022)
The Balinese indigenous people adopt the patrilineal family system, or paternity, or better known in the Balinese indigenous people as kepurusa or purusa. In accordance with the general principles adopted in the patrilineal family system, at least three basic principles are adopted in the purusa family system, among others the lineage traced from the line of man or father, in a woman's marriage is released from her legal relationship with her original family, as a result of marriage is the formation of a core family that ideally consists of father, mother and child. Whereas if a boy from a family that has only one son, will have a marriage with a daughter who comes from a family that has only one daughter, then there will be a debate between the family about the form which marriage to choose. If you choose the usual form of marriage, then the woman's family will definitely object, because the family will later become divorced. Similarly, on the contrary, if you choose the form of nyeburin marriage, then the family of the male party will object because it will also cause a state of hereditary rupture, or so-called ceput or putung. Therefore, women and men who are the only children in the family can have alternative marriages outside of the two forms of marriage above. The marriage is a double state marriage or in this case the husband does not enter the wife's family, and the wife will not enter the husband's family. Of course, it will bring different legal consequences from ordinary marriage or marriage to the marriage property, the position of the child, and his inheritance.In order to avoid a putung condition, a legal breakthrough is needed other than the usual form of marriage and the intermarriage, namely the negen dadua form of marriage. In Semarapura Kaja Village, there are several cases like this. For this reason, assistance is carried out in the context of increasing awareness and knowledge of the law of the inheritance rights of children in negen dadua marriage.